Risk and Refuge: Adolescent Boys’ Experiences of Violence in “Post-Conflict” Colombia - Browne, Amanda (Journal of interpersonal violence, 2021)
Increasingly, researchers and practitioners are examining connections between public and private cycles of violence. In complex emergency settings, these cycles of violence often intersect with conflicting norms and values as societies work toward sustainable peace. Gender norms, particularly norms of masculinity, are not often highlighted in transdisciplinary violence studies. Furthermore, few studies on either subject capture the perspectives and experiences of adolescent boys. This study seeks to explore adolescent boys’ (13-17 years) experiences with violence at home and in the community in “post-conflict” Colombia. Thematic qualitative analysis of 20 interview transcripts from 14 Colombian boys in Cundinamarca (n = 5) and Córdoba (n = 9) revealed themes of conflict avoidance, hegemonic masculinity, and opportunities for change in the form of positive coping habits. Further research into social and emotional coping behaviors and linkages to perpetuating violence between adolescence and adulthood is needed.